Effect of aluminum carbide interphase on the thermomechanical behavior of carbon nanotube/aluminum nanocomposites. (September 2019) - Shi, Xiaolong; Hassanzadeh Aghdam, Mohammad Kazem; Ansari, Reza
The objective of this work is to investigate the coefficient of thermal expansion of carbon nanotube reinforced aluminum matrix nanocomposites in which aluminum carbide (Al4 C3 ) interphase formed due to chemical interaction between the carbon nanotube and aluminum matrix is included. To this end, the micromechanical finite element method along with a representative volume element, which incorporates, carbon nanotube, interphase, and aluminum matrix is employed. The emphasis is mainly placed on the effect of Al4 C3 interphase on the coefficient of thermal expansion of aluminum nanocomposites with random microstructures. The effects of interphase thickness, carbon nanotube diameter, and volume fraction on the thermomechanical response of aluminum nanocomposite are discussed. The results reveal that the effect of Al4 C3 interphase on the coefficient of thermal expansion of the aluminum nanocomposites becomes more significant with (i) increasing the coefficient of thermal expansion volume fraction, (ii) decreasing the coefficient of thermal expansion diameter, and (iii) increasing the interphase thickness. It is clearly observed that the coefficient of thermal expansion varies nonlinearly with the carbon nanotube diameter; however, it decreases linearly as the carbon nanotube volume fraction increases. Furthermore, the axial and transverse coefficient of thermal expansions of aligned continuous and discontinuous carbon nanotube-reinforced aluminum nanocomposites with Al4 C3 interphase are predicted. Also, the presented finite element method results are compared with the available experiment in the literature, rule of mixture, and concentric cylinder model results.